From Lugos to Hollywood: Bela Lugosi’s transnational persona and the aural construction of Dracula in Tod Browning’s Dracula (1931) - Gabriela Hluscu; Marius-Mircea Crișan (Swedish Journal of Romanian Studies)
In horror literature, acoustic elements heighten sensory engagement and audience immersion in an atmosphere of dread, manipulate psychology, and help transcending the boundaries of imagination. Bram Stoker’s Dracula (1897) masterfully employs voice, sound, and silence to construct Count Dracula’s enigmatic presence, and intensify his uncanny duality as aristocratic seducer and primal predator. This paper examines how Tod Browning’s 1931 adaptation transposes Stoker’s acoustic strategies into cinematic language through Bela Lugosi’s vocal performance and the minimalist soundscape of the film, at the same time arguing that the transnational identity of the actor shaped Dracula’s Gothic allure. Bela Lugosi was born Béla Ferenc Dezső Blaskó in Lugos, Austria-Hungary (nowadays Lugoj, Romania), and adopted his stage name both as tribute to his hometown and due to its sonic resonance, that made it highly merchantable, a diasporic gesture that tied him forever to his Central-Eastern European origins, despite being marketed as an icon of exotic horror by Hollywood. Through close analysis of Lugosi’s voice, used with deliberate, hypnotic cadence in an English language with a Hungarian accent, and theatrical physicality, paired with the use of silence, diegetic sound, and Tchaikowsky’s Swan Lake motif, this study interrogates how auditory aesthetics and Lugosi’s embodiment of foreignness converged to craft Dracula’s enduring legacy. By bridging literary analysis with film studies, this work explores a central question: What facets of Lugosi’s personal charisma, theatrical training, and diasporic identity transformed his portrayal into a cultural archetype that continues to captivate audiences worldwide nearly a century later?